ANALISIS PENGARUH BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DAN KETIMPANGAN PENDAPATAN DI SUMATERA BARAT - Pranita, Yohana; Idris, Idris (Universitas Negeri Padang, 2020)
Abstrak : This study aims to determine and analyze the effect of capital expenditureon economic growth and income inequality in West Sumatra. This research isdescriptive and inductive. The data used in this study is secondary data with datacollection using panel data obtained from BPS West Sumatra Province 2014-2018period with 19 regencies / cities in West Sumatra. This study analyzed using asimultaneous equation model (simultaneous equation regression model). The resultsof this study indicate that (1) Capital Expenditures have a significant effect onEconomic Growth in West Sumatra (2) Capital Expenditures have no significanteffect on Income Inequality in West Sumatra (3) Simultaneously Capital Expendituresand Economic Growth have a significant effect on Income Inequality in WestSumatra.Keyword : Capital Expenditure, Economic Growth, Income Inequality